Study on Acute Oral Toxicity of Ethanolic Extract of Annonasquamosa Leaves in Mice (Musmusculus) - Khairunnisa; Dita Utami, Andini; Marianne (Indonesian Journal of Pharmaceutical and Clinical Research, 2018)
Abstract. The aims of this study were to determine the potential for acute oral toxicity of ethanolic extract of A.squamosa leaves with LD50 and the histopathological changes in liver and kidney of mice.This research used experimental method as per fixed dose method. The number of animals used in this research were 20 female mice. The study was divided into 2 steps, there were sighting and main studies. The control group was given Na-CMC 0.5%, the treatment groups were given ethanolic extract of A.squamosa leaves with doses of 5, 50, 300, 2,000 and 5,000 mg/kg bw. The results showed that the ethanolic extract of A.squamosa leaves with doses of 2,000 and 5,000 mg/kg bw did not show any toxicity signs. At a dose of 5,000 mg/kg bw caused hydropic degeneration, necrosis hepatocyte, glomerular atrophy, and tubular dilatation. There was no mortality was observed.It was estimated that LD50 of ethanolic extract of A.squamosa leaves was higher than 5,000 mg/kg bw and the extract were practically non-toxic. Keywords: Acute Toxicity, Annona squamosa, Ethanolic Extract